CONSULTATION IN THE POLICY PROCESS: DOUGLASIAN CULTURAL THEORY AND THE DEVELOPMENT OF ACCOUNTING REGULATION IN THE FACE OF CRISIS. (17th September 2015) - LINSLEY, PHILIP; MCMURRAY, ROBERT; SHRIVES, PHILIP
Abstract : This article employs Douglasian cultural theory to explain how policy consultations intended to secure meaningful reform can, in fact, work to reinforce the status quo. The context for this is an examination of responses to three consultations established by the Financial Reporting Council (FRC), the body responsible for regulating accounting and auditing in the UK. The results reveal a lack of diversity of voices in the responses to three consultations, with the enclave and isolate voices being significantly under‐represented despite the policy issues under debate being related to the financial crisis. Further, the initial pre‐consultation proposals are largely unchanged post‐consultation. We suggest that the regulator has not been captured; but instead is subject to what may be described as self‐capture. Self‐capture describes the instinctive reaction of a solidarity to act to uphold its pattern of social relations which results in the regulator's worldview inevitably (and unwittingly) being perpetuated.